Mode of schooling and academic performance among students in selected secondary schools in Ibadan North Local Government Area of Oyo State (2010)
The study examined the relationship between modes of schooling (day or boarding) on the academic performance of students from selected schools in Ibadan. Survey research design was adopted for the study. Purposive sampling technique was used to select 300 respondents from two boarding schools in Ibadan. The main instrument used for this study was a structured questionnaire. Data collected was analyzed using ANOVA to test the three hypotheses at 0.05 level of significance. The findings revealed that there is no significant difference in the performance of students in mathematics among boarding and day students. Findings also revealed that there is no significant difference among boarding and day students in their performance in English Language.